Pendampingan Edukasi dan Konsultasi Hukum untuk Meningkatkan Peran Hukum Dalam Mewujudkan Desa Aman dan Sejahtera di Desa Bulili - Dolot Alhasni Bakung; Zainal Abdul Aziz Hadju; Ramadhan Usman; Sofyan Piyo; Nurul Fazri Elfikri; Muhamad Khairun Kurniawan Kadir (Lembaga Pengembangan Kinerja Dosen, 2025)
Community service (PkM) in the form of educational assistance and legal consultation in Bulili Village, Duhiadaa Subdistrict, was carried out with the aim of improving legal understanding and assisting the community in resolving legal issues they face. This educational support and legal consultation activity was based on two crucial issues: the community's lack of understanding of marriage and inheritance laws, and their low participation in the village regulation formation process. These two issues were chosen because they significantly affect the realization of a safe, orderly, and prosperous village. The methods used in this community service program include interactive outreach and participatory-based direct consultation, combining educational and legal empowerment approaches for village residents. The results of the program indicate an increase in community legal awareness regarding rights and obligations within the family context, as well as the importance of active community involvement in the formulation of village regulations. It is hoped that this activity can strengthen the legal culture at the local level and serve as a foundation for the development of a just, inclusive, and sustainable village.